Automation Tool for Institutional Repositories Evaluation (2022)
The rise of digital repositories has framed a significant advance in access to academic and scientific knowledge, increasing its impact due to greater reach and lower cost. However, these platforms are a new topic that initially did not have standards or models to carry out their implementation and operation, which is why there were inconsistencies between repositories on issues such as interoperability, digital preservation, among others. Due to the lack of standardization and the exponential increase in the number of repositories, different organizations and researchers made multiple proposals to standardize the processes and characteristics of these platforms. The proposals materialized in models, such as the Dublin Core and DataCite metadata schemes, and in guides for the evaluation and implementation of repositories, such as the "Guide for the evaluation of institutional research repositories" by RECOLECTA or the DINI certificate (Deutsche Initiative für Netzwerk Information). The latter aim to evaluate the platforms in their entirety, including 8 sections with a total of 87 elements. Therefore, in this research an application was developed to automate the evaluation of repositories, automating processes that improve educational work using computer tools and their integration.